Ectopic differentiation of melanocyte stem cells is influenced by genetic background. (5th January 2015) - Harris, Melissa L.; Levy, Denise J.; Watkins‐Chow, Dawn E.; Pavan, William J.
Summary Hair graying in mouse is attributed to the loss of melanocyte stem cell function and the progressive depletion of the follicular melanocyte population. Single‐gene, hair graying mouse models have pointed to a number of critical pathways involved in melanocyte stem cell biology; however, the broad range of phenotypic variation observed in human hair graying suggests that additional genetic variants involved in this process may yet be discovered. Using a sensitized approach, we ask here whether natural genetic variation influences a predominant cellular mechanism of hair graying in mouse, melanocyte stem cell differentiation. We developed an innovative method to quantify melanocyte stem cell differentiation by measuring ectopically pigmented melanocyte stem cells in response to the melanocyte‐specific transgene Tg(Dct‐Sox10). We make the novel observation that the production of ectopically pigmented melanocyte stem cells varies considerably across strains. The success of sensitizing for melanocyte stem cell differentiation by Tg(Dct‐Sox10) sets the stage for future investigations into the genetic basis of strain‐specific contributions to melanocyte stem cell biology.